The Gambia : Technical Assistance Report-Public Investment Management Assessment. (IMF Staff Country Reports; Country Report ;, 2019)
This Technical Assistance Report on The Gambia highlights that the government has highlighted infrastructure development as a key element of National Development Plan, 2018-21. The report discusses that the need for increased public investment in the Gambia should be balanced against potential fiscal risks related to future Public-Private Partnerships and State-Owned Enterprise investments. Analysis of public investment patterns shows a fragmented picture, in which external financing dominates. Measures of the efficiency of infrastructure investments show mixed results and considerable room for improvement. The analysis explains that the Gambia's performance across different Public Investment Management Assessment (PIMA) indicators is mixed and does not compare favorably with regional counterparts. Nevertheless, there are many indicators where the PIMA rating is poor. Prevailing weaknesses include the presence of many information gaps and non-transparent disclosure policies. The mission's main recommendations focus on five priority areas and are designed to complement reforms that are already being undertaken.